Cidade flutuante: uma Manaus sobre as águas (1920-1967) - Souza, Leno José Barata (2010)
This work search expects to understand the city of Manaus enters the years of 1920 and 1967 from a specific subject: " The Floating City of Manaus" that, inside of this period, it was gradual if forming for the vast coast of the city, if becoming, in middle of the decade of fifty, a social and urban phenomenon produced by a proper culture of the place in which the relation with fluvial waters was always a strong characteristic in the life of the inhabitants of a certain region of amazonian hinterlândia. Talking with old inhabitants of the city of Manaus, over all with the former inhabitants of the floating city , the research looks for to rediscuss the Manaus of the period, just exit of gomífera its belle époque, traditionally clipped times, from a hegemonic memory, as maximum example of civilization and amazonense progress in contraposition to the historical time of this work, officially retaken for the lode of the lethargic and declining economic crisis. However, this exactly projected period, for example, to the light of the culture of the floating, while territories of the most varied sociabilities, can be surprised a vibrant and intriguing city that, through the most different experiences of housings, works and recreation was daily complained for its inhabitants. In this direction, the floating city , was without a doubt, the impactante social experience of this city in transformation. Almost unknown experiences for the Brazilian society, exactly the amazonense, little touched by a local official speech and/or rare contemplated by intellectual works, are classic or current they. Historiográfics gaps and silence that this work, throughout our reflections, tries to minimize e, especially for intermediary of the verbal narratives, look for to construct new histories and to project other times, always having as reference the culture of the floating housings that if it showed alive and present in the current days of the Manaus